Localized vitreous adhesion to the retina after ocular contusion with a baseball - Kimura M (Dove Medical Press, 2012)
Masayo Kimura, Akira Nishimura, Kazuhisa SugiyamaDepartment of Ophthalmology and Visual Science, Kanazawa University Graduate School of Medical Science, Kanazawa, JapanPurpose: To report a series of five cases of vitreous adhesions after blunt trauma caused by a baseball strike.Methods: The medical records of patients with ocular contusion after being struck by a baseball, who had undergone pars plana vitrectomy, were reviewed. An aqueous suspension of triamcinolone acetonide was used intraoperatively to facilitate visualization of the vitreous.Results: Five eyes were reviewed in this study. There were two cases of retinal detachment, two cases of traumatic macular hole, and one case of retinal detachment due to traumatic macular hole. Despite the surgical creation of posterior vitreous detachment, if not already present, the thin layer of localized vitreous adhesion to the retinal necrotic area with/without retinal hole was found between the major vascular arcades and the equator in all cases. The thin layer of the vitreous was removed with a vitreous cutter and diamond-dusted membrane scraper, but complete removal was impossible.Conclusions: A thin layer of localized vitreous adhesion at the area of retinal degeneration was observed in eyes following ocular contusion.Keywords: localized, vitreous adhesion, triamcinolone acetonide, ocular contusion, pars plana vitrectomy